Aspectos da exceção no Direito Internacional - França, Nathalia Penha Cardoso de (2019)
Exception took a different form in the 21st century, it is more subtle and almost imperceptible. A state of Exception is not decreed nor the legal order is suspended, but there are acts with measures of Exception within the democracies, living with the rule of law. The same is true in International Law. The international legal order has a hard core that gives human beings a minimal juridical protection. This jus cogens encompasses provisions of Human Rights and Humanitarian Law, limits the exercise of the internal and external sovereignty of States and is non-derogable, even in Exception. In addition, the legal emergency is a fraud, creating a pretext for authoritarian action by States in the international field. Analysing the metamorphosis of the concept of sovereignty, the genealogy of the Exception since Bonapartism and seeking elements for the defense of an international legal common ground, we begin to see aspects of the Exception also in International Law